Consumers' Preferences on Platform as a Service and SAP`s Engineering Response - Andrea Giessmann; Sven Feurer; Thomas Schneider; Stefan Wenzel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Platform as a service (PaaS) solutions are changing the way how software is produced, distributed, consumed, and priced. To be competitive on the market, PaaS providers have to be aware of drivers of successful platforms and design or adjust solutions accordingly. Surprisingly, prior research has made little attempt to investigate consumers' preferences on PaaS that influence developers' choice on PaaS solutions. This paper examines this understudied issue through a conjoint study. Based on the results, SAP`s engineering response is present in terms of SAP`s OnDemand Platform, SAP`s Business ByDesign Studio, SAP HANA Cloud solution as well as SAP`s Store.
Keywords: 330; platform-as-a-service; paas; enterprise software; enterprise platform; app store; platform business model; software ecosystem; Business software; Business model